Báo cáo về tình hình thực hiện Dự án hồ chứa nước Ka Pét, tỉnh Bình Thuận (Số: 381/BC- CP) - Chính phủ (2021)
Toàn văn Báo cáo về tình hình thực hiện Dự án hồ chứa nước Ka Pét, tỉnh Bình Thuận (Số: 381/BC- CP)